1974
DOI: 10.1002/app.1974.070180305
|View full text |Cite
|
Sign up to set email alerts
|

Binding of metal cations by natural substances

Abstract: SynopsisThe binding of mercuric chloride and other metal salts to bark, activated sludge (Milorganite), chitosan, poly(p-aminostyrene), and other natural and synthetic materials was investigated by specific atomic absorption and x-ray fluorescence spectroscopy. The synthetic poly(amin0styrene) was included for comparison with the natural polyamine chitosan. Our results show that a wide range of natural materials are potentially useful for the removal of toxic and precious metals that may be present in industri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(57 citation statements)
references
References 0 publications
1
52
1
3
Order By: Relevance
“…5,6 Chitosan is a hydrophilic, natural cationic polymer formed by the N-deacetylation of chitin, 7 which is present in fungi, insects, and crustaceans. Chitosan has been known for its metal adsorption properties since 1970s, 7,8 and it has been shown to effectively remove metals such as silver, 8 cadmium, 9 arsenic, 10 gold, 11,12 vanadium, 13 copper, [14][15][16] nickel, 14,17 chromium, 14,18 and mercury 17,19 from aqueous solutions. It was reported that the maximum adsorption capacity of chitosan for Hg 2þ was 815 mg/g.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Chitosan is a hydrophilic, natural cationic polymer formed by the N-deacetylation of chitin, 7 which is present in fungi, insects, and crustaceans. Chitosan has been known for its metal adsorption properties since 1970s, 7,8 and it has been shown to effectively remove metals such as silver, 8 cadmium, 9 arsenic, 10 gold, 11,12 vanadium, 13 copper, [14][15][16] nickel, 14,17 chromium, 14,18 and mercury 17,19 from aqueous solutions. It was reported that the maximum adsorption capacity of chitosan for Hg 2þ was 815 mg/g.…”
Section: Introductionmentioning
confidence: 99%
“…This result indicates that the DD is quite high, 12 therefore metal sorption should be important. 2,4 In this work we found the sorption capacity of chitin to be much less than that of raw crab shell. Other authors used chitosan with higher DD (94%), and obtained better results for metal removal.…”
Section: Results and Discussion Degree Of Deacetylationmentioning
confidence: 84%
“…5). One of the oldest publications on bark adsorption was the study of Masri et al (1974). In that study, Douglas fir and black oak barks were treated with mercury solutions and the adsorption quantities were 100 mg Hg/g for Douglas fir bark and 400 mg Hg/g for black oak bark.…”
Section: Barks and Metals Testedmentioning
confidence: 99%